2010
DOI: 10.1002/smll.201000864
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Polymer‐Grafted Multiwalled Carbon Nanotubes for In vitro Gene Delivery

Abstract: Carbon nanotubes (CNTs) consist of carbon atoms arranged in sheets of graphene rolled up into cylindrical shapes. This class of nanomaterials has attracted attention because of their extraordinary properties, such as high electrical and thermal conductivity. In addition, development in CNT functionalization chemistry has led to an enhanced dispersibility in aqueous physiological media which indeed broadens the spectrum for their potential biological applications including gene delivery. The aim of this study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(48 citation statements)
references
References 57 publications
1
46
1
Order By: Relevance
“…[1][2][3][4] Recent findings in nanomedicine have revealed that CNTs can be used as potential drug carriers, therapeutic agents and diagnostics tools as well. [5][6][7][8][9][10] In particular, due to their ability to cross cellular membranes, their nanosize dimension, high surface area and relatively good biocompatibility, CNTs have also been employed as a novel gene delivery vector system. [11][12][13] However, one of the major drawbacks is their low solubility and high propensity to aggregate in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Recent findings in nanomedicine have revealed that CNTs can be used as potential drug carriers, therapeutic agents and diagnostics tools as well. [5][6][7][8][9][10] In particular, due to their ability to cross cellular membranes, their nanosize dimension, high surface area and relatively good biocompatibility, CNTs have also been employed as a novel gene delivery vector system. [11][12][13] However, one of the major drawbacks is their low solubility and high propensity to aggregate in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Such broad applications of CNTs have led to an increased production level and thus increased concerns regarding human and environmental exposure. Further, given their applications in the biomedical field, [13,14] understanding how biological systems interact with this nanomaterial is urgently needed to create safer therapies, [14,15] and to regulate occupational exposures.…”
mentioning
confidence: 99%
“…The success of a gene therapy largely depends upon the activity induced by the target genes and the efficiency of gene delivery resulting from the combined effects of the delivery vector and the applied delivery route. 154 Various NPs have been investigated for gene delivery, including GNPs, 155 silver NPs, 156 CNTs, 157 liposomes, 158 polymersomes, 159 and polyplexes. Use of NPs enables targeting of tumor tissue through the EPR effect in gene therapy.…”
Section: Use Of Nanotechnology In Cancer Treatment Via Gene Therapymentioning
confidence: 99%